Cuci Tangan Pakai Sabun Menggunakan Model RANAS Di SD Negeri Klampis Ngasem 1 Surabaya: Indonesia - Andriani Masfufah, Maya (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
The RANAS model (Risk, Attitudes, Norms, Abilities, and Self-Regulation) is an easy-to-use method model for measuring behavioral elements, evaluating influences on behavior, creating customized plans to change behaviour, and measuring its effectiveness. Behavioral change strategies that target and modify behavioral factors in a given population can be designed and evaluated using a systematic behavior change approach. The aim of this brief review is to summarize the preliminary strategies in teaching children to wash hands and suggest strategies for teaching them to wash their hands. The core objective of this activity at SDN Klampis Ngasem I is fourth grade students consisting of four classes, namely 4A, 4B, 4C, and 4D. The RANAS model takes several months, but it is worth using. This method produces behavioral change strategies that (1) match the population, (2) effectively change behavior in the local environment, and (3) provide the basis for additional interventions. The behavior has not only been effectively modified, but also important ideas have been acquired to drive the local government for future projects. In the RANAS model there are three consequences considered: behavior, intention, and habit. Both behavior that is deemed appropriate and behaviour that is declared competitive is called "behavior".